Probing dark matter substructure in the gravitational lens HE 0435−1223 with the WFC3 grism. Issue 2 (7th June 2017) - Nierenberg, A. M.; Treu, T.; Brammer, G.; Peter, A. H. G.; Fassnacht, C. D.; Keeton, C. R.; Kochanek, C. S.; Schmidt, K. B.; Sluse, D.; Wright, S. A.
Abstract: Strong gravitational lensing provides a powerful test of cold dark matter (CDM) as it enables the detection and mass measurement of low-mass haloes even if they do not contain baryons. Compact lensed sources such as active galactic nuclei (AGNs) are particularly sensitive to perturbing subhaloes, but their use as a test of CDM has been limited by the small number of systems which have significant radio emission that is extended enough to avoid significant lensing by stars in the plane of the lens galaxy, and red enough to be minimally affected by differential dust extinction. Narrow-line emission is a promising alternative as it is also extended and, unlike radio, detectable in virtually all optically selected AGN lenses. We present first results from a Wide Field Camera 3 (WFC3) grism narrow-line survey of lensed quasars, for the quadruply lensed AGN HE 0435−1223. Using a forward modelling pipeline that enables us to robustly account for spatial blending, we measure the [O iii ] 5007 Å flux ratios of the four images. We find that the [O iii ] fluxes and positions are well fit by a simple smooth mass model for the main lens. Our data rule out a M 600 > 10 8 (10 7.2 ) M⊙ Navarro–Frenk–White perturber projected within ∼1.0 (0.1) arcsec of each of the lensed images, where M 600 is the perturber mass within its central 600 pc. The non-detection is broadly consistent with the expectations of ΛCDM for a single system. The sensitivity achieved demonstrates that powerful limits on the nature of dark matter can be obtained with the analysis of ∼20 narrow-line lenses.